PRODUCTION OF BIONAPHTHA FROM (C3-C5) PRIMARY ALCOHOLS VIA CATALYTIC DEHYDROGENATION/ DEHYDRATION PROCESSES - Coelho, Adonis [UNESP]; Metzker, Gustavo [UNESP]; Lima, Livia P. de [UNESP]; Gomes, Eleni [UNESP]; Boscolo, Mauricio [UNESP] (Soc Brasileira Quimica, 2025)
A sequence of dehydrogenation/dehydration reactions of homologous alcohols: propanol, butanol and pentanol was conducted using heterogeneous catalysts composed of mixed metal oxides basically of Mg and Al derived from hydrotalcites in the ratio M2+/Al3+ = 3, with 10 and 20% of the Mg substituted by Cu. The reactions were carried out in a fixed-bed reactor over a duration of 6 h at temperatures of 450 and 500 degrees C and yielded products of significant interest to the chemical industry. Product identification and quantification were achieved through gas chromatography coupled with mass spectrometry (GC-MS). A range of compounds were obtained, including alcohols, aldehydes, ethers, carboxylic acids, ketones, and hydrocarbons, with condensed alcohols and aldehydes being the predominant products. Reaction pathways were proposed for conversion of alcohols into their respective products, based on the Guerbet reaction mechanism. Catalysts containing copper proved to be more efficient in selectivity and stability throughout the reaction.
Keywords: homologous alcohols; Guerbet reaction; mixed metal oxides; bionaphtha.